The Fartlek training method with multiple valences: A review - Shukla, N.; Srivastava, A.; Agarwal, N. (International Journal of Innovative Science and Research Technology, 2023)
Running is concomitantly training, it is an opportunity to meet everyone`s need for solitude, but also a socializing factor; it can be practiced anywhere and anytime by social categories and at any age. Starting from the primary method of continuous effort, running is an exercise has been maximally exploited, it is a basic element in designing professional training sessions. Fartlek is a type of training that help both beginner or advanced runners to obtain a stronger favourable ground reaction and a faster pace. The paper reviews is the literature on this simple but efficient training means. It highlights the benefits of using fartlek and gives examples of fartlek sessions. This article can help normal population those who run for health, it alsoprovideguideline for those who make the transition from leisure to organized training, in their attempt to complete a long-distance training.